KAJIAN STUNTING DI KOTA SEMARANG - Widya Hary Cahyati; Galuh Nita Prameswari; Cahya Wulandari; Karnowo Karnowo (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
Stunting is a condition in which a child have a growth disorder, resulting from a lack of nutritional intake for a long time. The purpose of the study was to analyze the factors associated with the occurrence of stunting. This type of research is quantitative analytic research with a case-control design. Data collection methods through interviews and documentation. Based on the results of the study note that factors related to stunting at undergraduate in Semarang City in 2018 are mother's education level (OR = 2.97), mother's occupation (OR = 6.58), number of children (OR = 4.15), order of children (OR = 4.15), body length at birth (OR = 5.77), caregiver of children (OR = 9.99), exclusive breastfeeding status (OR = 3.47), income category (OR = 7.37), conditions home (OR = 3.78), and nutritional intake (OR = 8.79). Stunting handling policies that have been carried out in the City of Semarang related to the budget have been allocated to provinces and districts / cities, the Central Java Governor Regulation No. 85 of 2016 concerning the Action Plan for the Food and Nutrition Region of Central Java Province in 2015-2019. Suggestions that can be given to the department of religion in order to further enhance cooperation with the health center related to the maturity of marriage, knowledge about nutrition, including the importance of nutrition in the First 1000 Days of Life (1000 HPK); The Semarang city government should be able to include action plans for handling stunting, including improving the residential environment and increasing community capacity in the RPJMD.